Methanol fuel cell catalyst and preparation method thereof
The LaFeCoO3 perovskite metal oxide catalyst is supported by CeO2/r-GO composite material, which solves the precious metal problems of traditional catalysts, and achieves high-efficiency, stable and low-cost catalytic performance of methanol fuel cell, with anti-carbon monoxide poisoning ability and long-term service life .
Patent Information
- Application Number
- CN202411431288.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
Due to the scarcity and expensive precious metals, traditional methanol fuel cell catalysts have reduced kinetics, poor overpotentials, lack of stability and durability, and the uneven carbon support leads to poor metal-based dispersion, which increases costs and is difficult to meet high catalytic activity, stability and Low cost demand.
LaFeCoO3 perovskite metal oxides are loaded as catalysts by using CeO2/r-GO composites to prepare LaFeCoO3 by hydrothermal method, and the active sites are improved by using Co and Fe elements. The interface effect of CeO2 and r-GO enhances electron transfer and promotes LaFeCoO3 Interaction with the support improves catalytic efficiency.
It achieves high catalytic activity, stability, anti-carbon monoxide poisoning ability and durability, reduces fuel cell costs, does not contain precious metals, is environmentally friendly, and extends the service life of the catalyst.
Smart Images

Figure CN119297309A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and specifically refers to a methanol fuel cell catalyst and a preparation method thereof. Background Art
[0002] Methanol fuel cells have become increasingly popular due to their high safety, clean fuel, simple cell structure, and the ability to use methanol as a renewable fuel source. Liquid fuels such as methanol are attractive because they have high solubility in aqueous electrolytes and are easy to store or transport. In addition, methanol is inexpensive and easy to produce, which reduces the overall cost of the entire device, making it more practical and cost-effective.
[0003] Methanol fuel cell catalysts are usually composed of nanostructured noble metals (i.e., Pt) and metal-based alloys supported on carbon supports. However, these categories of metals are inherently scarce and expensive. Conventional electrocatalysts (i.e., Pt / C) are often characterized by reduced kinetics and poor overpotentials, and lack the stability and durability required for long-term fuel cell applications. These problems arise from undesirable side effects caused by carbon monoxide poisoning, metal dissolution, and surface oxidation. As a support for methanol fuel cell catalysts, it is necessary to maintain good catalytic performance without increasing costs. Therefore, carbon supports are not ideal because they are uneven and easily aggregated, resulting in poor dispersion of the metal matrix, thereby reducing the level of catalytic activity. To overcome all these defects, high noble metal loading is often required, which makes methanol fuel cells less cost-effective and therefore impractical. Therefore, the development of new electrocatalysts that simultaneously have high catalytic activity, excellent stability, resistance to carbon monoxide poisoning, and low cost has become a top priority for optimizing the use of fuel cells. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a methanol fuel cell catalyst and a preparation method thereof. The methanol fuel cell catalyst prepared by the present invention is composed of a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide, LaFeCoO3 has excellent ionic conductivity, overall corrosion resistance, good proton transport performance, high activity and stability, r-GO has a large specific surface area, and the doping of CeO2 further enhances the active area of the carrier, provides a large number of attachment sites for loading LaFeCoO3, improves the utilization rate of metal LaFeCoO3, and the interface effect between CeO2 and r-GO can enhance electron transfer and promote the interaction between LaFeCoO3 and the carrier, thereby improving the catalytic efficiency. The methanol fuel cell catalyst prepared by the present invention has the advantages of high catalytic activity, good stability, strong resistance to carbon monoxide poisoning and strong durability, and the metal catalyst and the carrier do not contain precious metals, which greatly reduces the overall cost of the fuel cell, and the metal catalyst and the carrier are relatively environmentally friendly during the preparation and reaction process, reducing the pollution of the fuel cell to the environment.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A methanol fuel cell catalyst is composed of a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide.
[0006] The preparation method of the CeO2 / r-GO composite material comprises the following steps: (1) Weigh 1-5 parts of graphite powder, 1.2-6 parts of potassium persulfate, and 0.75-3 parts of phosphorus pentoxide, stir in a 500 mL beaker, slowly add 20-100 parts of concentrated sulfuric acid, control the reaction at 85 °C for 3 h, cool to room temperature, mix the solution with 300-500 parts of deionized water, stir for 10 min, and let stand for 24 h. Filter the liquid to obtain a black solid, wash and dry; (2) adding concentrated sulfuric acid and potassium permanganate to the black solid obtained in step (1), wherein the amount ratio of the black solid, concentrated sulfuric acid and potassium permanganate is 5 g:5 mL:1 g, and then placing the obtained mixture in a 15°C low-temperature water bath for 10 min, raising the temperature to 40°C, stirring the mixture for 3 h, introducing 2-5 parts by volume of a 30% hydrogen peroxide solution to form an off-white precipitate, washing the precipitate with dilute hydrochloric acid and deionized water until the pH is adjusted to 6, and finally drying it to obtain graphene oxide; (3) Weigh 2-10 parts of graphene oxide obtained in step (2) and put them into a 500 mL conical flask, then add 300 parts of deionized water, then drop 2-10 parts of 10% cerium nitrate solution, stir thoroughly, and ultrasonicate for 30 minutes. After the reaction is completed, move the conical flask into an 85 ° C water bath and stir for 2 hours, add 25-50 parts of ammonia water, and react for 30 minutes; (4) The reaction mixture was placed in an oven and allowed to stand at 150 °C for 48 h. After cooling, it was filtered and washed. The filter cake was dried at 65 °C. The dried filter cake was then placed in a muffle furnace and calcined at 550 °C for 3 h under a nitrogen protective atmosphere to prevent adverse reactions or oxidation, thereby finally obtaining a CeO2 / r-GO composite material.
[0007] Furthermore, the simplified reaction equations involved in the preparation steps described in steps (1) to (3) are as follows: (1) C + K2S2O8 + P2O5 → graphite oxide precursor + other products (I); 2KMnO4 + 3H2SO4 → K2SO4 + 2MnSO4 + 3H2O + 5[O] (II); (2) C + [O] → C6H6O6 (III); H2O2 → H2O + [O] (IV); (3) r-GO + Ce(NO3)3 → r-GO-Ce 3+ (V); r-GO-Ce 3+ + 3NH3⋅H2O → Ce(OH)3 + r-GO + 3NH 4+ (VI); In the reaction equation (I), C is graphite powder, K2S2O8 is potassium persulfate, P2O5 is phosphorus pentoxide, KMnO4 is potassium permanganate, H2SO4 is concentrated sulfuric acid, MnSO4 is manganese sulfate, [O] is oxygen atom, C6H6O6 is graphene oxide, and r-GO-Ce 3+ is the reduced graphene oxide adsorbed by cerium ions, H2O2 in reaction equation (IV) is hydrogen peroxide, Ce(NO3)3 in reaction equation (V) is cerium nitrate, NH3⋅H2O in reaction equation (VI) is ammonia water, Ce(OH)3 is cerium hydroxide precipitate, NH 4+ It is the ammonium ion.
[0008] The preparation method of the LaFeCoO3 perovskite metal oxide comprises the following steps: (a) La(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O were dissolved in 30 parts of deionized water under magnetic stirring, citric acid was added, and ultrasonic dispersion was performed. The mixture was transferred into a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, which was sealed and kept at 180 °C for 12 h. After the autoclave was naturally cooled to room temperature, the precipitate was separated by centrifugation, and then dried in an oven at 80 °C to obtain a powder. (b) The powder was first heated to 500 °C at room temperature at a heating rate of 3 °C / min and kept at this temperature for calcination for 3 h. After calcination, it was further heated to 700 °C at a heating rate of 2 °C / min and kept at 700 °C for calcination for 3 h. The obtained LaFeCoO3 perovskite metal oxide was then stored in a desiccator.
[0009] Furthermore, in step (a), the molar ratio of La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid is 1:1:1:1.
[0010] The present invention also provides a method for preparing a methanol fuel cell catalyst, comprising the following steps: 1) LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material were dissolved in 30 parts of deionized water, the mass ratio of LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material was 5-10:1, and the mixture was dispersed evenly by magnetic stirring, and the solution was ultrasonically treated at 600 W for 45 min, and left at room temperature overnight to allow the ions to reach adsorption-desorption equilibrium, and the solution was centrifuged to wash the precipitate, and washed alternately with deionized water and anhydrous ethanol, and the obtained catalyst precursor was dried in an oven at 60 °C overnight; 2) The catalyst precursor obtained in step 1) was calcined at 700° C. for 2 h to obtain CeO2 / r-GO loaded LaFeCoO3 perovskite metal oxide.
[0011] Compared with the prior art, the present invention has the following beneficial effects: The methanol fuel cell catalyst prepared by the present invention is composed of CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide. The LaFeCoO3 prepared by a hydrothermal method has high crystallinity and good dispersibility. Due to the addition of Co, the promoting effect on the methanol oxidation reaction is more significant, which greatly improves the low-temperature reducibility and oxygen mobility of LaFeO3. The Co and Fe elements therein provide abundant active sites, which effectively promote the oxidation process of methanol. In addition, the oxygen storage capacity of CeO2 and the electronic conductivity of r-GO improve the oxygen reduction activity of the methanol fuel cell. The synergistic effect between the metal and the carrier jointly improves the overall catalytic efficiency of the catalyst. LaFeCoO3 is loaded on the CeO2 / r-GO composite material carrier, and its electronic conductivity is affected by the CeO2 / r-GO composite material carrier. The high electronic conductivity of r-GO helps to quickly transfer electrons and reduce the charge transfer resistance. CeO2 can play the role of an electron transfer bridge, further promoting the transfer of LaFeCoO3 to the CeO2 / r-GO carrier, and improving the catalytic efficiency. The poor conductivity of CeO2 limits its development in electrocatalysis. Combining it with r-GO improves the conductivity and dispersibility of CeO2, and promotes the rapid transport of electrolytes and the uniform dispersion of LaFeCoO3 nanoparticles. The presence of CeO2 alleviates the corrosion resistance of the carbon carrier and accelerates the adsorption and oxidation of carbon monoxide by hydroxyl groups on the surface. LaFeCoO3 with the addition of Co has a high tolerance to toxic intermediates such as carbon monoxide produced during methanol oxidation, greatly reducing the risk of catalyst poisoning caused by carbon monoxide adsorption. r-GO not only has a large specific surface area, but the doping of CeO2 further enhances the active area of the carrier, provides a large number of attachment sites for loading LaFeCoO3 nanoparticles, and improves the utilization rate of metal LaFeCoO3; and due to its complex structure and rich surface functional group structure, it provides good support for CeO2 nanoparticles, which is conducive to loading LaFeCoO3 on the carrier, preventing the agglomeration and sedimentation of catalyst particles, maintaining the exposure of catalyst active sites, and effectively protecting the catalyst from corrosion during the catalytic process of methanol fuel cells. r-GO can also serve as an electron transfer intermediate to enhance catalyst conduction. The interface effect between CeO2 and r-GO can enhance electron transfer and promote the interaction between LaFeCoO3 and the carrier, thereby improving the catalytic efficiency. Since the Co element added to LaFeCoO3 shows good chemical stability and structural stability as well as good proton transport performance in the catalytic process, it is relatively resistant to corrosion by acidic / alkaline electrolytes compared to platinum group metals, and the carrier improves the mechanical strength, thermal stability and durability of LaFeCoO3, prolongs the service life of the catalyst, and ensures the long-term use of the catalyst.The methanol fuel cell catalyst prepared by the present invention has the advantages of high catalytic activity, good stability, strong resistance to carbon monoxide poisoning and strong durability, and the metal catalyst and the carrier do not contain precious metals, which greatly reduces the overall cost of the fuel cell. The metal catalyst and the carrier are relatively environmentally friendly during the preparation and reaction process, which reduces the pollution of the fuel cell to the environment and has potential industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 The effective activity area bar graph of the catalysts obtained in Examples 1-3 of the present invention and Comparative Examples 1-3; Figure 2 It diagrams of the catalysts obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention; Figure 3 It is a long-term cycle stability diagram of the catalysts obtained in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0015] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0016] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0017] Example 1: This example provides a methanol fuel cell catalyst, which is composed of a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide.
[0018] The preparation method of the CeO2 / r-GO composite material comprises the following steps: (1) Weigh 1 part of graphite powder, 1.2 parts of potassium persulfate, and 3 parts of phosphorus pentoxide, stir in a 500 mL beaker, slowly add 20 parts of concentrated sulfuric acid, control the reaction at 85 °C for 3 h, cool to room temperature, mix the solution with 300 parts of deionized water, stir for 10 min, and let stand for 24 h. Filter the liquid to obtain a black solid, wash and dry; (2) Add 30 mL of concentrated sulfuric acid and 30 g of potassium permanganate to the black solid obtained in step (1), the amount ratio of the black solid, concentrated sulfuric acid and potassium permanganate is 5 g:5 mL:1 g, then place the obtained mixture in a 15 °C low-temperature water bath for 10 min, increase the temperature to 40 °C, stir the mixture for 3 h, introduce 2 parts of a 30% by volume hydrogen peroxide solution to form an off-white precipitate, wash the off-white precipitate with dilute hydrochloric acid and deionized water until the pH is adjusted to 6. Finally, dry it to obtain graphene oxide; (3) Weigh 2 parts of the graphene oxide obtained in step (2) and put them into a 500 mL conical flask, then add 300 parts of deionized water, then drop 10 parts of a 10% cerium nitrate solution, stir thoroughly, and ultrasonicate for 30 min. After the reaction is completed, move the conical flask into an 85°C water bath and stir for 2 h, add 25 parts of ammonia water, and react for 30 min to obtain a reaction mixture; (4) The reaction mixture was placed in an oven and allowed to stand at 150 °C for 48 h. After cooling, it was filtered and washed. The filter cake was dried at 65 °C. The dried filter cake was then placed in a muffle furnace and calcined at 550 °C for 3 h under a nitrogen protective atmosphere to prevent adverse reactions or oxidation, thereby finally obtaining a CeO2 / r-GO composite material.
[0019] The preparation method of the LaFeCoO3 perovskite metal oxide comprises the following steps: (a) La(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O were dissolved in 30 parts of deionized water under magnetic stirring, and citric acid was added. The molar ratio of La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid was 1:1:1:1. Ultrasonic dispersion was performed for 30 min, and the mixture was transferred into a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and kept at 180°C for 12 h. After the autoclave was naturally cooled to room temperature, the precipitate was separated by centrifugation, washed with deionized water and anhydrous ethanol for multiple times, and then dried in an oven at 80°C to obtain a powder. (b) The powder was first heated to 500 °C at room temperature at a heating rate of 3 °C / min and kept at this temperature for calcination for 3 h. After calcination, it was further heated to 700 °C at a heating rate of 2 °C / min and kept at 700 °C for calcination for 3 h. The obtained LaFeCoO3 perovskite metal oxide was then stored in a desiccator.
[0020] This embodiment also provides a method for preparing a methanol fuel cell catalyst, comprising the following steps: 1) LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material were dissolved in 30 parts of deionized water, with the mass ratio of LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material being 5:1. The mixture was evenly dispersed by magnetic stirring, and the solution was ultrasonically treated at 600 W for 45 min. The solution was left at room temperature overnight to allow the ions to reach adsorption-desorption equilibrium. The solution was centrifuged and washed to precipitate, and the solution was washed alternately with deionized water and anhydrous ethanol. The obtained catalyst precursor was dried in an oven at 60 °C overnight. 2) The catalyst precursor obtained in step 1) was calcined at 700° C. for 2 h to obtain CeO2 / r-GO loaded LaFeCoO3 perovskite metal oxide.
[0021] Example 2: This example provides a methanol fuel cell catalyst, which is composed of a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide.
[0022] The preparation method of the CeO2 / r-GO composite material comprises the following steps: (1) Weigh 3 parts of graphite powder, 3.6 parts of potassium persulfate, and 1.8 parts of phosphorus pentoxide in a 500 mL beaker, stir, slowly add 60 parts of concentrated sulfuric acid, control the reaction at 85 °C for 3 h, cool to room temperature, mix the solution with 400 parts of deionized water, stir for 10 min, let stand for 24 h, filter out the liquid to obtain a black solid, wash and dry; (2) Add concentrated sulfuric acid and potassium permanganate to the black solid obtained in step (1), the amount ratio of concentrated sulfuric acid to potassium permanganate is 5 g:5 mL:1 g, then place the obtained mixture in a 15°C low-temperature water bath for 10 min, increase the temperature to 40°C, stir the mixture for 3 h, introduce 3 parts of a 30% by volume hydrogen peroxide solution to form an off-white precipitate, and wash the precipitate with dilute hydrochloric acid and deionized water until the pH is adjusted to 6. Finally, dry it to obtain graphene oxide; (3) Weigh 7.5 parts of the graphene oxide obtained in step (2) and put it into a 500 mL conical flask, then add 300 parts of deionized water. Subsequently, add 7.5 parts of a 10% cerium nitrate solution dropwise, stir thoroughly, and ultrasonicate for 30 minutes. After the reaction is completed, move the conical flask into an 85°C water bath and stir for 2 hours. Add 35 parts of ammonia water and react for 30 minutes to obtain a reaction mixture; (4) The reaction mixture was placed in an oven and allowed to stand at 150 °C for 48 h. After cooling, it was filtered and washed. The filter cake was dried at 65 °C. The dried filter cake was then placed in a muffle furnace and calcined at 550 °C for 3 h under a nitrogen protective atmosphere to prevent adverse reactions or oxidation, thereby finally obtaining a CeO2 / r-GO composite material.
[0023] The preparation method of the LaFeCoO3 perovskite metal oxide is the same as that in Example 1.
[0024] This embodiment also provides a method for preparing a methanol fuel cell catalyst, comprising the following steps: 1) LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material were dissolved in 30 parts of deionized water, with the mass ratio of LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material being 8:1. The mixture was evenly dispersed by magnetic stirring, and the solution was ultrasonically treated at 600 W for 45 min. The solution was left at room temperature overnight to allow the ions to reach adsorption-desorption equilibrium. The solution was centrifuged and washed to precipitate, and the solution was alternately washed with deionized water and anhydrous ethanol. The obtained catalyst precursor was dried in an oven at 60 °C overnight. 2) The catalyst precursor obtained in step 1) was calcined at 700° C. for 2 h to obtain CeO2 / r-GO loaded LaFeCoO3 perovskite metal oxide.
[0025] Example 3: This example provides a methanol fuel cell catalyst, which is composed of a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide.
[0026] The preparation method of the CeO2 / r-GO composite material comprises the following steps: (1) Weigh 5 parts of graphite powder, 6 parts of potassium persulfate, and 3 parts of phosphorus pentoxide, stir in a 500 mL beaker, slowly add 100 parts of concentrated sulfuric acid, control the reaction at 85 °C for 3 h, cool to room temperature, mix the solution with 500 parts of deionized water, stir for 10 min, let stand for 24 h, filter out the liquid to obtain a black solid, wash and dry; (2) adding concentrated sulfuric acid and potassium permanganate to the black solid obtained in step (1), wherein the amount ratio of the black solid, concentrated sulfuric acid and potassium permanganate is 5 g:5 mL:1 g, and then placing the obtained mixture in a 15°C low-temperature water bath for 10 min, raising the temperature to 40°C, stirring the mixture for 3 h, introducing 5 parts of a 30% by volume hydrogen peroxide solution to form an off-white precipitate, washing the precipitate with dilute hydrochloric acid and deionized water until the pH is adjusted to 6, and finally drying it to obtain graphene oxide; (3) Weigh 10 parts of the graphene oxide obtained in step (2) and put them into a 500 mL conical flask, then add 300 parts of deionized water. Subsequently, drop 2 parts of a 10% cerium nitrate solution, stir thoroughly, and ultrasonicate for 30 minutes. After the reaction is completed, move the conical flask into an 85°C water bath and stir for 2 hours. Add 50 parts of ammonia water and react for 30 minutes to obtain a reaction mixture; (4) The reaction mixture was placed in an oven and allowed to stand at 150 °C for 48 h. After cooling, it was filtered and washed. The filter cake was dried at 65 °C. The dried filter cake was then placed in a muffle furnace and calcined at 550 °C for 3 h under a nitrogen protective atmosphere to prevent adverse reactions or oxidation, thereby finally obtaining a CeO2 / r-GO composite material.
[0027] The preparation method of the LaFeCoO3 perovskite metal oxide is the same as that in Example 1.
[0028] This embodiment also provides a method for preparing a methanol fuel cell catalyst, comprising the following steps: 1) LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material were dissolved in 30 parts of deionized water, the mass ratio of LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material was 10:1, and the mixture was dispersed evenly by magnetic stirring. The solution was ultrasonically treated at 600 W for 45 min and left at room temperature overnight to allow the ions to reach adsorption-desorption equilibrium. The solution was centrifuged and washed to precipitate, and the solution was washed alternately with deionized water and anhydrous ethanol. The obtained catalyst precursor was dried in an oven at 60 °C overnight. 2) The catalyst precursor obtained in step 1) was calcined at 700° C. for 2 h to obtain CeO2 / r-GO loaded LaFeCoO3 perovskite metal oxide.
[0029] Comparative Example 1: Compared with Example 1, Comparative Example 1 eliminates the addition of CeO2, and the rest is the same as Example 1.
[0030] Comparative Example 2: Compared with Example 1, Comparative Example 2 eliminates the addition of r-GO, and the rest is the same as Example 1.
[0031] Comparative Example 3: 5 mg of commercial Pt / C (Johnson Matthey company, loading 20%) and 100 μL of Nafion117 solution were ultrasonically dispersed for 30 min to obtain a solution. 10 μL of the above solution was drop-coated on a rotating disk electrode and dried at room temperature to obtain a thin film electrode.
[0032] Experimental example: 1. Catalytic activity The catalytic performance of methanol fuel cells was determined by cyclic voltammetry. The catalysts used in Examples 1-3 and Comparative Examples 1-3 for methanol fuel cells were used. 3.8 mg of each group was weighed and dispersed in 1 μL of ethanol. Ultrasonic dispersion was performed for 30 min. 30 μL of the ethanol dispersion of each group of catalysts was drop-coated on the surface of the glassy carbon working electrode. After standing for 15 min to dry, 10 μL of Nafion117 solution was drop-coated on the surface. The solution was stood for 15 min to dry and used. A 1 M CH3OH / 0.5 M H2SO4 solution was prepared and tested using an electrochemical workstation (CHI660D). The electrochemical workstation was turned on, the point electrode was connected, and the electrode was immersed in a 1 MCH3OH / 0.5 M H2SO4 solution. Nitrogen was bubbled for 20 min. The parameters of the electrochemical workstation were set to work mode CV, a scan rate of 50 mV / s, a scan voltage of -0.3 V-1 V, and a scan cycle was performed. The electrochemical effective active area (ESA) of the catalyst can be calculated by deducting the double-layer hydrogen adsorption and desorption charge method. ESA=Q H / (0.21×[Pt]), where Q H (mC·cm -2 ) represents the average value of the electrochemical adsorption and desorption of hydrogen on the surface, [Pt] represents the loading of the catalyst per unit area on the electrode (mC cm -2 ), and 0.21 (mC·cm -2 ) represents the amount of electricity required for the oxidation of a monolayer of H2 on the surface of a smooth Pt catalyst. Similarly, the active area of LaFeCoO3 perovskite metal oxide as a catalyst is the same. The larger the ESA of the catalyst, the higher the electrocatalytic activity. The calculated ESA data are shown in Table 1. The graph drawn based on the data is shown in the attached figure. Figure 1 shown.
[0033] 2. Stability The stability of the methanol fuel cell was tested by chronoamperometry. The preparation method of each group of catalysts was the same as the catalytic activity test procedure, except that the chronoamperometry curve was obtained by using an electrochemical workstation in an argon-saturated 1 M CH3OH / 0.5 M H2SO4 aqueous solution at a potential of 0.5 V for 3600 s. After 3600 s steady-state chronoamperometry, the current densities of Examples 1-3 and Comparative Examples 1-3 were plotted as shown in the attached figure. Figure 2 The long-term cycling stability of the prepared catalyst in 1M CH3OH / 0.5M H2SO4 solution was tested by cyclic voltammetry. Figure 3 shown.
[0034] 3. Anti-carbon monoxide poisoning ability The long-term poisoning rate δ is an indicator to measure the stability of the electrocatalyst to poisoning. The lower the δ value, the better the stability of the electrocatalyst. It can be calculated using the formula δ=100 / J0×(dJ / dt), where dJ / dt is the slope of the current decay, and J0 is the initial current obtained by extrapolation. J0 is calculated by extrapolation based on the obtained chronoamperometric curve, and the slope of the current decay part is studied to obtain the dJ / dt value of the electrocatalyst. The long-term poisoning rate is calculated, and the results are shown in Table 1.
[0035] Table 1
[0036] Table 1 and Figure 1 The results show that the effective active area of the embodiment group is significantly higher than that of the comparative examples 1-3. However, it can be seen from comparative examples 1-3 that the effective active area of LaFeCoO3 perovskite metal oxide as a metal catalyst is also higher than that of the traditional Pt noble metal catalyst, indicating that LaFeCoO3 perovskite metal oxide as a methanol fuel cell catalyst has great potential to replace noble metals such as Pt. The long-term poisoning rate in Table 1 also shows that the methanol fuel catalyst prepared by the present invention has good resistance to carbon monoxide poisoning and can be used for a long time. Figure 2 As shown, during the whole constant potential scanning process, the catalyst prepared in the embodiment has a significantly higher current density than the comparative example after 3600 s steady-state chronoamperometric test; Figure 3 The long-term cycle stability diagram of the catalysts obtained in Examples 1-3 of the present invention and Comparative Examples 1-3 is shown. After 1000 cycles, the stability of the catalyst prepared by the present invention is significantly higher than that of the commercial Pt / C catalyst.
[0037] In summary, through the verification of the embodiments and comparative examples, it can be seen that the methanol fuel cell catalyst formed by the CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide in the present invention has high catalytic activity, high stability and high resistance to carbon monoxide poisoning, and the present invention does not use precious metals, which greatly reduces the cost of methanol fuel cells.
[0038] The present invention and its implementation methods are described above, and the described embodiments are only some embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. Based on this, other specific implementation methods of the present invention obtained by ordinary technicians in the field under the inspiration of the technical solution without creative labor should fall within the protection scope of the present invention.
Claims
1. A methanol fuel cell catalyst, characterized in that: The methanol fuel cell catalyst is composed of CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide; The mass ratio of the CeO2 / r-GO composite material to the LaFeCoO3 perovskite metal oxide is 5-10:1; The preparation method of the CeO2 / r-GO composite material comprises the following steps: (1) Weigh 1-5 parts of graphite powder, 1.2-6 parts of potassium persulfate, and 0.75-3 parts of phosphorus pentoxide, stir and mix, slowly add 20-100 parts of concentrated sulfuric acid, heat to react, cool to room temperature, add 300-500 parts of deionized water to the mixed solution, stir and mix, let stand, filter, wash and dry to obtain a black solid; (2) adding concentrated sulfuric acid and potassium permanganate to the black solid obtained in step (1), then placing the obtained mixture in a water bath, stirring and mixing, introducing 2-5 parts by volume of a 30% hydrogen peroxide solution to form an off-white precipitate, washing the off-white precipitate with dilute hydrochloric acid and deionized water until the pH is adjusted to 6, and finally drying it to obtain graphene oxide; (3) Weigh 2-10 parts of the graphene oxide obtained in step (2), add deionized water, then dropwise add 2-10 parts of a 10% cerium nitrate solution, stir thoroughly and sonicate. After the reaction is completed, move the mixture into a water bath and stir, add 25-50 parts of aqueous ammonia to obtain a reaction mixture; (4) placing the reaction mixture obtained in step (3) into an oven, filtering and washing after cooling, drying the filter cake, and then calcining the dried filter cake to obtain a CeO2 / r-GO composite material; The preparation method of the LaFeCoO3 perovskite metal oxide comprises the following steps: (a) La(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O were dissolved in deionized water under magnetic stirring, citric acid was added, ultrasonic dispersion was performed, and hydrothermal reaction was carried out. After cooling to room temperature naturally, the precipitation was separated by centrifugation, and dried to obtain powder; (b) The powder is calcined to obtain LaFeCoO3 perovskite metal oxide.
2. A methanol fuel cell catalyst according to claim 1, characterized in that: The amount ratio of the black solid, concentrated sulfuric acid and potassium permanganate in step (2) is 5 g:5 mL:1 g.
3. A methanol fuel cell catalyst according to claim 1, characterized in that: The water bath temperature in step (2) is 15°C, the stirring time is 10 min, then the water bath temperature is increased to 40°C, the stirring time is 3 h, the oven temperature in step (4) is set to 150°C, the time is set to 48 h, and the calcination in step (4) is carried out under a nitrogen protective atmosphere, the temperature is set to 550°C, and the time is 3 h.
4. A methanol fuel cell catalyst according to claim 1, characterized in that: The molar ratio of La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid in step (a) is 1:1:1:
1. The temperature of the hydrothermal reaction in step (a) is set to 180°C and the time is set to 12 h. The calcination in step (b) is first heated to 500°C at a heating rate of 3°C / min at room temperature and maintained at this temperature for calcination for 3 hours. After the calcination is completed, it is further heated to 700°C at a heating rate of 2°C / min and maintained at 700°C for calcination for 3 hours.
5. A method for preparing a methanol fuel cell catalyst according to any one of claims 1 to 4, characterized in that: The specific preparation process is as follows: 1) dissolving LaFeCoO3 perovskite metal oxide and CeO2 / r-GO composite material in deionized water, stirring and dissolving, then ultrasonically treating, centrifuging the solution, washing the precipitate, and drying overnight to obtain a catalyst precursor; 2) The catalyst precursor obtained in step 1) is calcined at 700° C. for 2 h to obtain a CeO2 / r-GO composite material loaded with LaFeCoO3 perovskite metal oxide.
6. The method for preparing a methanol fuel cell catalyst according to claim 5, characterized in that: The ultrasonic treatment described in step 1) is carried out in an ultrasonic cleaning machine with a power setting of 600 W and a time setting of 45 min.